Perbandingan Pemberian Konsentrasi ZPT IAA dan Air Kelapa Terhadap Pertumbuhan Stek Tanaman Vanili (Vanilla planofolia) - Sulistianingtyas, Indah; Kurnia, Theresa Dwi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to obtain the effect of immersion in various consentrations of ZPT IAA and the length of coconut water immersion on the growth of vanilla cuttings. The research was conducted from August to November 2024 located in the greenhouse of the Faculty of Agriculture and Business, Satya Wacana Christian University, Salatiga City, Central Java. This study used a Randomized Group Design (RAK), Consists of 6 treatments with 4 replications including: Control (P0), immersion of cuttings in ZPT IAA with concentrations of 200 ppm (P1), 250 ppm (P2), and 300 ppm (P3), and immersion of coconut water for 12 hours (P4), and 24 hours (P5). Parameters observed included shoot emergence time, shoot length, shoot diameter, root length, number of roots, and number of leaves. Data were analyzed using ANOVA analysis variance with 5% BNT further test. The results showed that immersion with ZPT IAA concentration of 200 ppm and 12 hours of coconut water immersion was able to accelerate the time of bud emergence. In the treatment of coconut water immersion for 24 hours is able to give a real effect on the length of shoots, shoot diameter, root length, and number of roots. The results showed that this treatment provided the best growth for vanilla cuttings.